Codification or personalization: a consideration on the suitable approach for organizations - Supar, Norizah (2013)
Knowledge is an organization’s best sustainable source of competitive advantage and knowledge management is considered a key part of the strategy of using expertise to create a sustainable competitive advantage. In order to transform knowledge into a valuable organizational asset, knowledge, experience and expertise must be formalized, distributed, shared and applied. Knowledge sharing is, therefore, one of the key processes in knowledge management. This paper is based on part of a larger study to understand factors that affect knowledge sharing among academic staff in Malaysian higher academic institutions. Previous research has identified several factors that affect knowledge sharing. However, further research needs to be carried out to ascertain factors that affect knowledge sharing, in particular among higher academic institutions in Malaysia. Its relevance to higher academic institutions is especially pertinent considering that being a center of learning, a higher level of knowledge sharing among the teaching staff could bring about an increased level of productivity or performance and satisfaction in the workplace. The outcome of this study will enable further understanding on knowledge sharing behavior of academic staff and may therefore contribute towards successful implementation of knowledge sharing as part of organizational knowledge management initiatives. Based on non-random, criterion, purposive sampling, three higher academic institutions from the Klang Valley area of the State of Selangor, Malaysia were selected to be included in the study. Findings from 194 respondents in the organizations under study indicated that codification is not positively related to knowledge sharing. However, based on previous research conducted, this paper wishes to highlight the importance of personalization approach and that this approach may apply in certain types of organizations instead of codification. Alternatively, a balanced or mixed approach of both codification and personalization may be utilized.